Neural effects of oxytocin and mimicry in frontotemporal dementia: A randomized crossover study. (10th November 2020) - Oliver, Lindsay D.; Stewart, Chloe; Coleman, Kristy; Kryklywy, James H.; Bartha, Robert; Mitchell, Derek G.V.; Finger, Elizabeth C.
Abstract : Objective: To determine whether intranasal oxytocin, alone or in combination with instructed mimicry of facial expressions, would augment neural activity in patients with frontotemporal dementia (FTD) in brain regions associated with empathy, emotion processing, and the simulation network, as indexed by blood oxygen–level dependent (BOLD) signal during fMRI. Methods: In a placebo-controlled, randomized crossover design, 28 patients with FTD received 72 IU intranasal oxytocin or placebo and then completed an fMRI facial expression mimicry task. Results: Oxytocin alone and in combination with instructed mimicry increased activity in regions of the simulation network and in limbic regions associated with emotional expression processing. Conclusions: The findings demonstrate latent capacity to augment neural activity in affected limbic and other frontal and temporal regions during social cognition in patients with FTD, and support the promise and need for further investigation of these interventions as therapeutics in FTD. ClinicalTrials.gov identifier: NCT01937013. Classification of evidence: This study provides Class III evidence that a single dose of 72 IU intranasal oxytocin augments BOLD signal in patients with FTD during viewing of emotional facial expressions.